Gender differences in global antimicrobial resistance - Salehi, Mahkameh; Laitinen, Ville; Bhanushali, Shivang; Bengtsson-Palme, Johan; Collignon, Peter; Beggs, John J.; Pärnänen, Katariina; Lahti, Leo (Springer Science and Business Media LLC, 2025)
Antimicrobial resistance is one of the leading causes of mortality globally. However, little is known about the distribution of antibiotic resistance genes (ARGs) in human gut metagenomes, collectively referred to as the resistome, across socio-demographic gradients. In particular, limited evidence exists on gender-based differences. We investigated how the resistomes differ between women and men in a global dataset of 14,641 publicly available human gut metagenomes encompassing countries with widely variable economic statuses. We observed a 9% higher total ARG load in women than in men in high-income countries. However, in low- and middle-income countries, the difference between genders was reversed in univariate models, but not significant after adjusting for covariates. Interestingly, the differences in ARG load between genders emerged in adulthood, suggesting resistomes differentiate between genders after childhood. Collectively, our data-driven analyses shed light on global, gendered antibiotic resistance patterns, which may help guide further research and targeted interventions.